Neutrophil-Mediated Endogenous Analgesia Contributes to Sex Differences in Oral Cancer Pain - Scheff, Nicole N.; Bhattacharya, Aditi; Dowse, Edward; Dang, Richard X.; Dolan, John C.; Wang, Susanna; Kim, Hyesung; Albertson, Donna G.; Schmidt, Brian L. (Frontiers in Integrative Neuroscience, 2018)
The incidence of oral cancer in the United States is increasing, especially in young people and women. Patients with oral cancer report severe functional pain. Using a patient cohort accrued through the New York University Oral Cancer Center and immune-competent mouse models, we identify a sex difference in the prevalence and severity of oral cancer pain. A neutrophil-mediated endogenous analgesic mechanism is present in male mice with oral cancer. Local naloxone treatment potentiates cancer mediator-induced orofacial nociceptive behavior in male mice only. Tongues from male mice with oral cancer have significantly more infiltrating neutrophils compared to female mice with oral cancer. Neutrophils isolated from the cancer-induced inflammatory microenvironment express beta-endorphin and met-enkephalin. Furthermore, neutrophil depletion results in nociceptive behavior in male mice. These data suggest a role for sex-specific, immune cell-mediated endogenous analgesia in the treatment of oral cancer pain.